The Role of Non-Governmental Organizations on Development of population Concepts A Field Study in Lattakia city - ياسين , أحلام عبد الهادي; مبيض, مهند محمد; جوني, مريم زهير (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aimed to identify role of non-governmental organizations on development of population concepts in Lattakia city, from the point of view board members who work in it, and identify the differences in means of members answers about role of non-governmental organizations on development of population concepts in Lattakia city according to the variables (years of experience, scientific achievement). To achieve the object of the research used the descriptive method and a questionnaire has been included (49) items, included two axises, the first: the extent of the contribution of NGOs in creating the factors that help in developing the concepts of population education, and the second: the methods used by the society in developing the concepts of population education, then applied to a sample of (62) members in non-governmental organization in Lattakia city for the year 2019, validity of the questionnaire was established though a jury of (7) specialized arbitrators. Also it was confirmed by its application to a survey sample of 16 members by using the Alpha-Cronbach coefficient, which was (0.864) and (0.972) by the Spearman Brown coefficient. The research concluded the following results: The role of non-governmental organizations on development of population concepts in Lattakia city, from the point of board members was middle degree. There are found statistically significant differences between the means of members answers about role of non-governmental organizations on development of population concepts in Lattakia city according to the variable years of experience in favor of more than 5 years. There are found statistically significant differences between the means of board members answers about role of non-governmental organizations on development of population concepts in Lattakia city according to the variable scientific achievement in favor of license and postgraduate studies campaign.